Organoids and mini-organs - Davies, Jamie A.; Lawrence, Melanie L. (Academic Press, 2018)
Organs and Mini-Organs combines contributions from leading practitioners who work under the editorial control of an acclaimed researcher who also served for eight years as Editor-in-Chief of the journal Organogenesis, the first journal on this topic. The book begins with an introduction, but then delves into chapters that present advice on how to make organoids for many systems. In addition, case studies that illustrate the uses of organioids are presented, along with discussions on future directions and specific problems that need to be solved